Internationalism. National-liberation movement and our epoch. [With contribs of N. Kolikov, K. Brutents (KI. Brutenc), R. Ulyanovsky (R. Ul'janovskij) a.o.]. Vol. 2 (Novosti Press Agency)
Original title: Internacionalizm. Nacional'no-osvoboditel'noe dviženie: naša epocha.